Pathogenesis of Cardiac Depression in Acute Destructive Pancreatitis - A. V. Ershov; V. T. Dolgikh; O. V. Korpacheva; V. V. Rusakov; N. I. Taran; N. S. Gritsenko (Общая реаниматология, 2016)
Objective is to identify the pathogenic factors for progression of pancreatogenic cardiac failure in the nearest and remote periods.Materials and methods. The study was carried out on 130 male Wistar rats (292±4.0 g) divided into 4 groups. The animals were anesthetized with ethyl ether. Acute destructive pancreatitis was simulated in three experimental groups by infusion of bile (0.15 ml/kg body weight) taken from the bile duct into the pancreatic tissue. The isolated isovolumically contracting rat heart (according to E. L. Fallen et al) was simulated 24 hours, 7 days and 1 month after the bile infusion. The pressure in the left ventricle was measured by electric manometer BMT and registered along with the first derivative at the device N3384P calculating the systolic and diastolic blood pressure, and the speed of contraction and relaxation. At the same time the perfusate samples passed through the coronary arteries were har vested, and aspartate aminotransferase (AST) and glucose were determined by standard methods. To identify the cardiac depression, the high contraction rhythm and hypercalcemic and hypoxic perfusion were applied.Results. It was found that in acute destructive pancreatitis the power and speed parameters of the heart con tractile function were altered that led to lowering the systolic blood pressure and velocity of contraction and relax ation of the left ventricular myocardium and increased diastolic blood pressure as an indicator of cardyomyocyte contracture rate. These abnormalities were evidently manifested in increased heartbits, including hypercalcemic and hypoxic perfusion of the isolated hearts. Glucose consumption was raised per each mmHg generated by the ventricular pressure.Conclusion. the most significant pathogenetic factors of pancreatogenic heart failure include hypoxia, car diomyocyte membrane destruction, inhibition of sarcolemma Capump, sarcoplasmic reticulum, and mitochondrial dysfunction. The maximum depression of myocardial contractility of the left ventricle is detecting during the first day and in a month after simulated pancreatic necrosis.